ANALYZING THE RELATIONSHIP BETWEEN THE IOD (INDIAN OCEAN DIPOLE) AND ENSO (EL NIÑO–SOUTHERN OSCILLATION) ON SEA SURFACE TEMPERATURE AND RAINFALL VARIABILITY IN THE WATERS OF WEST SUMATERA - Maatitawaer, Natasya Debora C; Rifardi, Rifardi; Ilahi, Ilham; Mubarak, Mubarak; Tanjung, Afrizal; Basiluddin, Fadhlan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
This research examines the influence of the Indian Ocean Dipole (IOD) and El Niño–Southern Oscillation (ENSO) on sea surface temperature (SST) and rainfall variability in the coastal waters of West Sumatra over the period 2014–2024. The analysis draws on the Dipole Mode Index (DMI), Niño 3.4 index, SST, and rainfall data, processed using MathWorks and Excel. Regression analysis between field and satellite-derived SST data showed a strong correlation (R² = 0.936), confirming the reliability of satellite data for this study. Findings reveal that positive IOD and El Niño events are generally associated with cooler SSTs and reduced rainfall. In contrast, negative IOD and La Niña phases correspond to warmer SSTs and increased rainfall. The IOD appears to exert a more pronounced influence on SST variability than ENSO. Notably, the combined occurrence of a positive IOD and El Niño amplifies the decline in SST and rainfall. At the same time, the combination of a negative IOD and La Niña enhances increases in these variables. These results highlight the significant role of large-scale climate mode in shaping regional oceanographic and atmospheric conditions in the West Sumatra region.